Corporate Governance and Strategic Decision Making - Okechukwu Lawrence Emeagwali (IntechOpen, 2017)
This edited volume aims to intimate and orient readers on the current state of corporate governance and strategic decision making a decade after the global financial crises. In particular, it sheds more light on the current state of affairs of corporate governance mechanisms, codes, and their enforcement as well as novel issues arising. The ten constituent chapters contained herein are authored by seasoned academics with research interests in the areas of corporate governance, strategic management, and sustainable management practices. It provides up-to-date theoretical and empirical evidence of such corporate governance issues as corporate governance codes, corporate fraud, quality of earnings, strategic decision making, corporate social responsibility, sustainable management, and sustainable growth strategies. Irrespective of the diverse nature and span of the topics included, this edited volume is divided into three sections and structured to read as a unit.
English
Keywords: Sustainable Management Practices; Business Administration; Social Sciences and Humanities; Management and Economics; Business